GnRH-Induced Ca2+ Signaling Patterns and Gonadotropin Secretion in Pituitary Gonadotrophs. Functional Adaptations to Both Ordinary and Extraordinary Physiological Demands - Durán-Pastén, María Luisa; Fiordelisio, Tatiana (Frontiers in Endocrinology, 2013)
Pituitary gonadotrophs are a small fraction of the anterior pituitary population, yet they synthesize gonadotropins: luteinizing (LH) and follicle stimulating (FSH), essential for gametogenesis and steroidogenesis. LH is secreted via a regulated pathway while FSH release is mostly constitutive and controlled by synthesis. Although gonadotrophs fire action potentials spontaneously, the intracellular Ca2+ rises produced do not influence secretion, which is mainly driven by Gonadotropin Releasing Hormone (GnRH), a decapeptide synthesized in the hypothalamus and released in a pulsatile manner into the hypophyseal portal circulation. GnRH binding to G protein coupled receptors triggers Ca2+ mobilization from InsP3-sensitive intracellular pools, generating the global Ca2+ elevations necessary for secretion. Ca2+ signaling responses to increasing [GnRH] vary in stereotyped fashion from subthreshold to baseline spiking (oscillatory), to biphasic (spike-oscillatory or spike-plateau). This progression varies somewhat in gonadotrophs from different species and biological preparations. Both baseline spiking and biphasic GnRH-induced Ca2+ signals control LH/FSH synthesis and exocytosis. Estradiol and testosterone regulate gonadotropin secretion through feedback mechanisms, while FSH synthesis and release are influenced by activin, inhibin and follistatin. Adaptation to physiological events like the estrous cycle, involves changes in GnRH sensitivity and LH/FSH synthesis: in proestrus, estradiol feedback regulation abruptly changes from negative to positive, causing the pre-ovulatory LH surge. Similarly, when testosterone levels drop after orquiectomy the lack of negative feedback on pituitary and hypothalamus boosts both GnRH and LH secretion, gonadotrophs GnRH sensitivity increases and Ca2+ signaling patterns change. In addition, gonadotrophs proliferate and grow. These plastic changes denote a more vigorous functional adaptation in response to an extraordinary functional deman